Akutversorgung des Patienten mit schwerem Schädel-Hirn-Trauma - Juratli, Tareq; Stephan, Adrian (Der Anaesthesist, 2015)
BackgroundTraumatic brain injury (TBI) is a leading cause of death and permanent disability and a common and important global problem. The contribution of secondary posttraumatic brain damage to overall disability in TBI is significant, underlining the importance of prompt and comprehensive treatment for affected patients.MethodsThis article focuses on current concepts of prehospital and emergency room management of patients with severe TBI to prevent secondary brain injuries.Results and discussionPreclinical prevention and treatment of hypoxia, hypotension and hypercarbia are essential, as they affect the long-term outcome in TBI patients. Prehospital intubation should be critically weighed and in the context of an individual decision. In general, prehospital intubation is more difficult than in the clinical setting. The combination of ketamine and benzodiazepines are commonly used to induce anesthesia before intubation in hemodynamic instable patients. The choice of a muscle relaxant for anesthesia induction is either a non-depolarizing neuromuscular blocking agent or succinylcholine. Administration of mannitol or hypertonic saline is effective to rapidly decrease intracranial pressure. Whenever possible the final destination for transport of TBI patients should be a level I center with round the clock neurosurgical expertise. Trauma-induced coagulopathy should be recognized and immediately treated using a point-of-care testing.ConclusionHypoxia, hypotension and hypercarbia should strictly be avoided to improve survival and neurological outcome in patients with severe TBI. The prehospital decision to intubate must be made on a case by case basis at the accident site. A level I trauma center should be the destination for this patient group.